Global population genetics and diversity in the TAS2R bitter taste receptor family - Wooding, Stephen P.; Ramirez, Vicente A. (Frontiers in Genetics, 2022)
Bitter taste receptors (TAS2Rs) are noted for their role in perception, and mounting evidence suggests that they mediate responses to compounds entering airways, gut, and other tissues. The importance of these roles suggests that TAS2Rs have been under pressure from natural selection. To determine the extent of variation in TAS2Rs on a global scale and its implications for human evolution and behavior, we analyzed patterns of diversity in the complete 25 gene repertoire of human TAS2Rs in ~2,500 subjects representing worldwide populations. Across the TAS2R family as a whole, we observed 721 single nucleotide polymorphisms (SNPs) including 494 nonsynonymous SNPs along with 40 indels and gained and lost start and stop codons. In addition, computational predictions identified 169 variants particularly likely to affect receptor function, making them candidate sources of phenotypic variation. Diversity levels ranged widely among loci, with the number of segregating sites ranging from 17 to 41 with a mean of 32 among genes and per nucleotide heterozygosity (π) ranging from 0.02% to 0.36% with a mean of 0.12%. FST ranged from 0.01 to 0.26 with a mean of 0.13, pointing to modest differentiation among populations. Comparisons of observed π and FST values with their genome wide distributions revealed that most fell between the 5th and 95th percentiles and were thus consistent with expectations. Further, tests for natural selection using Tajima’s D statistic revealed only two loci departing from expectations given D’s genome wide distribution. These patterns are consistent with an overall relaxation of selective pressure on TAS2Rs in the course of recent human evolution.